DYNAMICS OF THE RURAL INDIAN ECONOMY: A COMPREHENSIVE STUDY - Kumar Bharat; Vishwa Suresh (Journal of Accounting Research, Utility Finance and Digital Assets, 2023)
This research article presents a comprehensive study on the dynamics of the rural Indian economy. With a focus on understanding the key sectors, evaluating government policies, exploring technology's role, and analyzing challenges and opportunities, this study aims to provide insights into the intricacies of rural economic development. Through an in-depth examination of the primary sectors driving the rural economy, including agriculture, livestock, forestry, handicrafts, and rural industries, the research uncovers their economic significance, interdependencies, and growth potential. The assessment of government policies and initiatives sheds light on their impact on income generation, employment opportunities, infrastructure development, and market access in rural areas. the study explores the transformative power of technology and innovation in rural economic development. It investigates successful models and interventions that leverage technology to enhance productivity, value chain integration, and market access in rural sectors. The research also addresses the challenges faced by the rural Indian economy, such as agrarian distress, limited access to finance, inadequate infrastructure, and climate change impacts. By identifying opportunities for sustainable development, such as diversification of rural livelihoods, promotion of entrepreneurship, and strengthening of rural-urban linkages, this study aims to contribute to the advancement of rural economic growth and prosperity.